STUDI META-ANALISIS TENTANG HUBUNGAN ANTARA STRESS KERJA DENGAN PRESTASI KERJA - Hardani Widhiastuti (Faculty of Psychology, Universitas Gadjah Mada, 2002)
This article provides a meta-analysis of the relationship between Job Stress and Job Performance. The Quantitative review includes 17 correlations from 15 studies. Result indicated that ρ = .7567; both the .0805 credibility and 1.4329 confidence intervals (95%). Keywords: meta analysis, job stress, job performance